Avaliação da influência do método, grau, umidade e energia de compactação na resistência ao cisalhamento de um solo da cidade de Alegrete/RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The shear strength is the main characteristic in soil’s rupture analysis. The soil ability to resist to shear forces is directly liked to its compaction degree. To reach a higher compaction degree with lower energy, its increase the soil’s water content until it reach an optimum moisture determined in laboratory. There are large amounts of earth dams used for water retention purposes to irrigation and quench animal thirst in western region of Rio Grande do Sul. These constructions, located in state’s interior, hardly ever feature appropriate technological control and even compaction is not realized with correct equipment, because of hard access to this locations. In this context, were realized a number of 64 direct shear tests, consolidated, slow and saturated, in samples of a clayey-sand soil, static and dynamically compacted under many different water content and compaction degree. It was possible to verify the influence of compaction water content in the peak shear strength for normal stresses smaller than overconsolidation stress. In the other hand, there was not verified significant influence in friction angle and cohesion. This behavior is due, mainly, to the fact that peak shear strength values for normal stresses higher than overconsolidation stress, presents similar results in mostly, adjusting the failure envelope to the shame values. It was noted that, possibly, the way tests were executed was not the best to analyze the influence of desired characteristics, since an influence’s part may have been lost during saturation and consolidation process. Besides that, the compaction methods were not proper to verify its influence in shear strength, because do not feature enough characteristics to change compacted soil’s structure. Testing in samples with higher range of water content and compaction degree than the ones that were analyzed can aggregate to an additional study.
Keywords: Engenharia civil; Resistência; Cisalhamento; Compactação dos solos; Civil engineering; Resistance; Shear; Soil compaction; CNPQ::ENGENHARIAS